Biosynthesis of Selenium Nanoparticles from Plant Extract Majidea Zanguebarica and Investigation of their Hepatoprotective Activity - Dhunaa Krishnamoorthy; Flory Shobana Mariya; Kavithaa Krishnamoorthy; Geetha Mani; Kalpana Devi Mohan; Panimalar Abirami Karuppusamy; Roselin Gnanarajan; Arul Narayanaswamy (Nanochemistry Research)
Selenium Nanoparticles (SeNPs) represent a promising adjunct for numerous disorders. SeNPs provide a potentially advantageous hepatoprotective effect due to their capacity to protect the liver from oxidative stress induced by chemicals or infections. Green synthesis offers numerous advantages for nanoparticle generation compared to physical and chemical approaches. It does not require substantial energy consumption or the utilization of hazardous and toxic substances. This study utilized the leaf extract of Majidea zanguebarica for the green production of SeNPs and examined their hepatoprotective effects on HepG2 cells in vitro. SeNPs were effectively produced utilizing the plant extract of Majidea zanguebarica as a reducing agent. Characterization investigations utilizing UV-Vis spectroscopy, X-ray diffraction (XRD), and Fourier-transform infrared spectroscopy (FTIR) validated the synthesis of stable and spherical SeNPs. The hepatoprotective efficacy of SeNPs was evaluated utilizing HepG2 cells. Cell viability assays and the recovery of inflamed cells were conducted to assess the protective effects against induced liver injury. The findings revealed a dose-dependent cytoprotective impact of Majidea zanguebarica-synthesized SeNPs, as indicated by enhanced cell survival, achieved through the examination of critical signaling pathways associated with hepatoprotection. The expression levels of ROS, GSH, and GSH/GSSG were examined, indicating the potential of bio-synthesized SeNPs in alleviating hepatotoxicity. This research offers significant insights into the production of SeNPs derived from Majidea zanguebarica and highlights their hepatoprotective effectiveness against HepG2 cells. The environmentally sustainable method of synthesizing SeNPs with plant extracts adheres to the principles of sustainable nanotechnology, underscoring the promise of these nanoparticles for liver health applications.